Breeding of Fructilactobacillus sanfranciscensis with excellent ethanol tolerance based on adaptive evolution technology. Issue 1 (8th February 2023) - Liu, Yan; Danial, Muhammad; Dong, Huixin; Zhang, Min; Jia, Ru; Zhang, Guohua
Abstract: Fructilactobacillus (F.) sanfranciscensis LS1 is one of the dominant strains in sourdough. Ethanol produced during fermentation is an inevitable stress factor for this stain. At present, the research on the mechanism of ethanol stress in lactic acid bacteria is limited compared to yeast species (particularly Saccharomyces (S.) cerevisiae ). In this study microbial physiology and protein expression analysis technology was used. F. sanfranciscensis LS1 served as the original bacteria, and evolutionary bacteria LS1‐1 were obtained by adaptive evolution. The comparison of the two strains' growth, survival rate, morphology, hydrophobicity, cohesive force and protein expression revealed that the evolved bacteria had a significantly higher ethanol tolerance than the original bacteria. Similarly, the hydrophobicity of evolved bacteria was increased about 6.6 times than that of the original bacteria. With an increase in ethanol concentration, the level of damage on evolved bacteria was less, and the total proportion of damaged cells decreased. After 8 h of culturing, the self‐cohesion of the evolved strain was 1.29 times more than the original strain. Sodium dodecyl‐sulfate polyacrylamide gel electrophoresis analysis has shown that the number of protein bands of the evolved bacteria LS1‐1 increased significantly, indicating that the associated proteins were expressed more and the strain's ability to resist environmental pressure was improved. Abstract : Adaptive laboratory evolution breeding of Fructilactobacillus sanfranciscensis with high tolerance to ethanol.